ANALISIS UKURAN PERUSAHAAN MEMODERASI LIKUIDITAS DAN LEVERAGE TERHADAP LABA BERSIH PADA BANK MUAMALAT INDONESIA - Harahap, Ainul Yusna; Lubis, Nurliza (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
This research is about the analysis of the size of companies that moderate liquidity and leverage on the net profit of Islamic banks, namely Bank Muamalat Indonesia in Langsa City. The results of the study will be processed using the Statistical Package for the Social Sciences. The research methods used are the Instrument Test, Classical Assumption Test, and Hypothesis Test. The results of this study show that liquidity has a significant positive influence on the bank's net profit. Likewise, leverage also has a significant positive effect on the bank's net profit. However, after moderation with the size of the company, it does not provide a significant interaction between liquidity and leverage on net income. Future research can use expanded research samples and exploration of other variables.